From Smart Field Devices to Industrial IoT: The Evolution of Asset Intelligence and the Pioneering Role of Honeywell Field Device Manager - Anil Mankali Masakal (International Journal of Computational and Experimental Science and Engineering, 2026)
The Industrial Internet of Things represents a fundamental shift in the monitoring, configuration, and optimization of industrial assets throughout their lifecycle. Long before the term "IIoT" entered mainstream usage, the process automation industry began embedding digital intelligence directly into field instruments such as transmitters, valves, and analyzers. This article looks at how moved from using simple analog instruments to advanced smart field devices, discusses the importance of open communication standards like the Highway Addressable Remote Transducer protocol, Device Description Language, and Electronic Device Description Language, and explores how Honeywell Field Device Manager became a leading platform for connecting smart devices. This article shares insights from my work at Honeywell FDM from 2003 to 2011, where I moved from being a founding software engineer to a project lead, and it highlights important advancements in design, communication methods, and standard practices that allowed for remote setup, troubleshooting, and management of industrial devices on a large scale. These innovations materially influenced industry standards, competitive platforms, and the technological foundations of modern IIoT systems.